Invalidity - Chen-Wishart, Mindy; Sono, Hiroo; Vogenauer, Stefan, 1968- (Oxford : Oxford University Press, 2022)
The 'Studies in the Contract Laws of Asia' series charts the divergence in and common principles of contract laws across Asia, with a view to providing the scholarly foundations for future harmonization and reform. This fourth volume deals with factors affecting the validity of contracts.
This edition also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 2, 2022).
Keywords: Performance (Law) -- Asia; Contracts -- Asia; Comparative law -- Asia; Law; Laws of specific jurisdictions & specific areas of law